2019
DOI: 10.1080/13102818.2019.1626283
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of crab haemocyanin against clinical pathogens

Abstract: The increasing antibiotic resistance among pathogenic bacteria is a challenge that drives the development of new antibacterial substances. Marine inhabitants are excellent sources of antimicrobial proteins and considered as promising candidates for the treatment of microbial infections. In the present study, we obtained haemocyanin from Eriphia verrucosa and studied its potential to suppress the growth of some pathogenic bacteria and yeasts. The putative antibacterial molecules were isolated from the haemolymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The studies on sequence diversity of this class of proteins and their subunit composition are mostly related to crustacean adaptation to environmental challenges. In recent years, the research on the structure of Hc in arthropods like in mollusks is also focused on the presence of N- and O-glycans, which are a prerequisite for their usage as therapeutic agents in bacterial, viral, and cancer treatment because many glycans act as receptors for bacteria, viruses, and other pathogens [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies on sequence diversity of this class of proteins and their subunit composition are mostly related to crustacean adaptation to environmental challenges. In recent years, the research on the structure of Hc in arthropods like in mollusks is also focused on the presence of N- and O-glycans, which are a prerequisite for their usage as therapeutic agents in bacterial, viral, and cancer treatment because many glycans act as receptors for bacteria, viruses, and other pathogens [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of O-glycosylation of EvHc5 was confirmed by antimicrobial assay of the subunits 1–5 isolated from the native Hc of E. verrucosa [ 52 ]. The authors reported the potential of subunit 1, 2, and 5 to be used as substitutes of some commonly used antibiotics to which bacterial resistance has been developed like E. coli and B. subtilis and other bacterial pathogens ( S. epidermidis , S. enterica , S. aureus , and P. aeruginosa ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] In addition to their application in cancer immunotherapy, some of the hemocyanins show potential as antibacterial and/or antiviral agents. [10,11,12] Despite that many hemocyanins were isolated and very well chemically and structurally characterized many years ago, their direct cytotoxic effect on various cancer cell lines have been scarcely studied. Few studies demonstrated that KHL added at a concentration of 500 μg/mL to estrogen-independent breast cancer cell lines (ZR75-1) and pancreatic cancer (PANC-1) inhibited the cell growth by 40% for 72 h. [13] It, however, had a weaker effect on the estrogen-dependent breast cancer cells (MCF-7) and androgen-independent prostate cancer cells (DU 145) for which was estimated a reduction of the cell viability only with 19% and 6%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations also focused on the immunological properties of hemocyanin in arthropods. The antibacterial activity of malacostracean hemocyanin against clinical pathogens or molecular diversity changes of the white shrimp hemocyanin related to pathogen infection are current examples [17,18].…”
Section: Introductionmentioning
confidence: 99%